Adorando a Deméter. Euno-Antíoco y la diosa de Enna - Sánchez León, María Luisa (Gerión. Revista de Historia Antigua, 2005)
The analysis of the sources allows to affirm that during the first bellum servile in Sicily the insurgents rendered cult to Demeter, specially venerated in the sacred city of Enna, capital of the slave kingdom. It can be infered from the information provided by Cicero in the Verrines that Eunus-basileus Antiochus had under his control the sanctuary of the goddess. This fact is confirmed by one of the four series that integrate at the moment the coinage of basileus Antiochus.
Keywords: Roman Sicily; religion; bellum servile; literay sources; numismatic